Smart content selection for public displays in ambient intelligence environments - Ribeiro, Fernando Reinaldo (2014)
A public display that is able to present the right information at the right time is a very compelling concept. However, realising or even approaching this ability to autonomously select appropriate content based on some interpretation of the surrounding social context represents a major challenge. This article provides an overview of the key challenges involved and an exploration of some of the main alternatives available. It also describes a novel place-based content adaptation system that autonomously selects from web sources the content deemed more relevant according to a dynamic place model. This model is based on a tag cloud that combines content suggestions expressed by multiple place visitors with those expressed by the place owner. Evaluation results have shown that a place tag cloud can provide a valuable approach to this issue and that people recognize and understand the sensitivity of the system to their demands.